Syllis ergeni: a new species of Syllidae (Annelida: Polychaeta) from Izmir Bay (Aegean Sea, eastern Mediterranean Sea) - Çinar, Melih Ertan (Zootaxa, 2005)
The faunal analysis of hard bottom materials collected from Alsancak Harbour and its vicinity (Izmir Bay, Aegean Sea) revealed a new syllid species, Syllis ergeni. The species is mainly characterized by having a dark-brown colour pattern on the dorsum of anterior and middle segments, short blade falcigers, the number and morphology of aciculae, and a pigmented proventriculus and pharynx. The morphology, ecology, distribution and reproductive features of the species are explained and discussed.